A PROSPECTIVE STUDY ON DRUG UTILIZATION IN OBSTETRIC PROCEDURES WITH EMPHASIS ON ANTIBIOTIC USAGE AT A TERTIARY CARE HOSPITAL - Sachdeva, Shikha; Chaudhary, Aarti; Nain, Parminder; Santpur, Unmesh (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Antibiotics are largely prescribed drugs in all major surgical procedures due to high prevalence of infections that has been increase in expenditure and increases antibacterial resistance. Drug utilization studies help to identify and overcome the misuse of antibacterial in prescribing pattern. Hence, the aim of this study was to evaluate the antibiotics utilization patterns in obstetric procedures. Methods: It is a prospective observational study carried out in department of obstetrics and gynecology, of a multi-specialty teaching hospital (Haryana) after obtaining permission from the IEC. The prescriptions were assessed for patient’s demographic data, antimicrobial preference, dose, duration, and route of administration. Categorization of drugs according to Food and Drug Administration (FDA), and rationality score as per the World Health Organization (WHO). Results: During six month study period 120 patients were included into study. The mean age of women undergoing C-section procedure was 27.79±2.78 years. The maximum (90.83%) length of hospital stay was 2 week by women under C-section procedure. The single antibiotic therapy (ceftriaxone - 53.33%) was the most commonly prescribed antibiotic as prophylaxis but in post- operative prescription orders, triple antibiotic combination therapy (ceftriaxone, metronidazole with gentamycin) was maximum (62.50%) prescribed antibiotic. Parenteral route (96.09% in pre-operative and 59.40% in post-operative) was most common route for antibiotic administration. Out of 2216 drugs, branded drugs were 1893 (85.42%) and generic drugs were 323 (14.58%). Conclusion: The present study facilitates the rational use of ceftriaxone as prophylaxis in C-section and triple antibiotic combination therapy as post-operative by the gynaecologists. These antibiotics are most effective without any adverse effect on mother and fetus when use in recommended dose and frequency during obstetric procedures. Keywords: Antibiotics, Caesarean section delivery, Drug utilization study